Analysis of the Value of Moral Education in the Novel "Teruslah Bodoh Jangan Pintar" by Tere Liye (A Literary Sociology Study) - Prasetyo Adi Putra; Iib Marzuqi; Hendrik Furqon (Journal of Social Research, 2025)
The central research problem addresses how literature functions as both a medium for character education and social criticism, specifically investigating what moral education values are embedded in the novel and how various forms of social injustice are portrayed through character interactions and social contexts. This study aims to analyze the moral education values and forms of social injustice depicted in Tere Liye’s novel Teruslah Bodoh Jangan Pintar through a literary sociology approach. This research employs qualitative descriptive methods with reading and note-taking techniques for data collection. The results show that the novel contains various moral education values, including creativity, justice, hard work, responsibility, honesty, and empathy with social care. Additionally, the novel depicts eight forms of social injustice: economic inequality, gender discrimination, social class oppression, educational injustice, racial-ethnic-religious discrimination, legal injustice, labor exploitation, and structural-cultural violence. Through Faruk’s sociology of literature theory, this novel serves not only as fiction but also as a medium for social criticism and character education that reflects Indonesian social reality. The implications demonstrate that literature serves as an effective medium for moral education and social awareness, with this novel functioning not only as entertainment but also as a catalyst for critical consciousness about systemic social problems. The balanced distribution of both moral values and forms of social injustice indicates the author’s intentional effort to provide comprehensive social commentary while promoting character development, making this work valuable for educational purposes and social transformation.